2015
DOI: 10.1186/s13099-015-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

Description of Campylobacter jejuni Bf, an atypical aero-tolerant strain

Abstract: BackgroundCampylobacter jejuni is a leading cause of bacterial enteritis worldwide. This microaerophilic bacterium can survive in aerobic environments, suggesting it has protective mechanisms against oxidative stress. The clinical C. jejuni Bf strain is characterized by an increased resistance to oxygen. This study aimed to characterize the behavior of the clinical C. jejuni Bf strain under an aerobic atmosphere and in response to ROS-promoter agents.MethodsGrowth was studied in both aerobic and microaerobic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 56 publications
2
53
0
1
Order By: Relevance
“…In addition, Rodrigues et al (2015) recently characterized an unique human isolate of C. jejuni strain, named Bf, which can grow aerobically, suggesting that some C. jejuni strains are highly resistant to aerobic stress. Increased tolerance to aerobic stress would enable C. jejuni to survive during transmission to humans through foods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rodrigues et al (2015) recently characterized an unique human isolate of C. jejuni strain, named Bf, which can grow aerobically, suggesting that some C. jejuni strains are highly resistant to aerobic stress. Increased tolerance to aerobic stress would enable C. jejuni to survive during transmission to humans through foods.…”
Section: Discussionmentioning
confidence: 99%
“…Rodrigues et al (2015) recently reported the aerobic growth of C. jejuni strain Bf on Karmali agar. For this strain visible growth was reported within 24 h of aerobic incubation at 42°C.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to C. coli OR12 Aer, growth in liquid medium could not be elicited, and a quantitative assay was used to measure growth on solid medium. Superior resistance to peroxide stress was also noted compared to C. jejuni NCTC 11168, which had failed to grow aerobically (Rodrigues et al, 2015). Growth on solid medium creates oxygen gradients, such that facultative anaerobes have been found to be more active on the bottom layer and aerobes more rapidly dividing on the top layer of colonies (Reyrolle and Letellier, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some strains are able to better counteract aerobic conditions for their survival. Recently, the atypical C. jejuni Bf was described to be able to grow under aerobic conditions in contrast to other C. jejuni (Rodrigues et al, 2015, 2016). As for C. jejuni Bf, C. coli OR12 is also able to develop an habituation to aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%